Avaliação, in vitro, dos parâmetros cinéticos da enzima acetilcolinesterase cerebral de ratos frente a alguns compostos azóis - Serres, Jonas Daci da Silva (2011)
The acetylcholinesterase enzyme is responsible for the acetylcholine hydrolisis in the synaptic cleft during the transmission of nervous impulse. The investigation of new inhibitors of this important enzyme is very relevant on tentative to minimize the effects due damages on cholinergic transmission, mainly in pathologies as Alzheimer s disease. Therefore, this work has investigated the inhibitory potencial of different classes of heterocyclic compounds (pyrazole, isoxazole and isoxazolinone), in vitro, on the acetylcholinesterase activity on different cerebral structures of rats (cortex, striatum and hippocampus). Among all tested compounds, only the 2c compound did not show any inhibition; all the remaining compounds showed significative inhibition (p<0,05), and the compounds 2a and 3c, that shown the best inhibitory efficacy (51 and 59 %, respectively), were the compounds selected to the kinetic enzimatic assays. From these results it was possible to characterize the kinetic parameters (Km and VMAX) and the inhibition type showed by every compound through the Lineweaver-Burk and Cornish-Bowden plots. The mentioned parameters to the compound 2a were Km = 0.2 mM and VMAX = 7.94 μmoles ASCh/h/mg of protein. The compound exihibited a competitive inhibition type with Ki = 1.46 mM. To the compound 3c, the values of Km and VMAX were 0.05 and 1.42 μmoles ASCh/h/mg of protein, respectively. This compound performed a noncompetitive inhibition type with Ki = 2.2 mM. All the compounds were previously diluted in methanol PA in concentrations of 0.031 mM, 0.0625 mM, 0.125 mM, 0.250 mM and 0.500 mM. The inhibitors selected to the kinetic assays were also diluted in methanol PA in the concentrations of 0.125, 0.250, 0.500 and 1.0 mM.